Interpersonal conflicts at work and knowledge hiding: Moderating role of interactional justice and mediating role of workplace well-being - Javeria Irshad; Fozia Malik; Sania Sarfraz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
The objective of this study is to examine the correlation between interpersonal conflicts at work and knowledge hiding. It also aims to determine the mediating effect of workplace well-being and the moderating impact of interactional justice. The study also explores how interpersonal conflicts at work and workplace well-being are influenced by interactional justice in Pakistan's IT industry. First, the conceptual model that links the research's main elements was theoretically grounded in pertinent literature. Second, data was obtained from 300 marketing managers of IT-based enterprises with a branch in a developing country via a structured questionnaire survey. Finally, analysis is done using SPSS software and to test the hypotheses, regression analysis is used. Findings of this study demonstrate that interpersonal conflicts at work are positively associated with knowledge hiding. Additionally, the link between interpersonal conflicts at work and well-being is influenced by interactional justice. This paper also provides marketing managers of IT sector with practical advice on how to deal with workplace interpersonal problems.
Keywords: 330; Interpersonal conflicts at work; workplace well-being; knowledge hiding; interactional justice; conservation of resource theory